2015
DOI: 10.1134/s2079059715030156
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the Md-Exp7 gene for the biosynthesis of expansin in wild species of the genus Malus Mill.

Abstract: Molecular genetic analysis revealed a polymorphism for the Md Exp7 gene that controls the bio synthesis of expansin in wild species of the genus Malus. Eight allelic forms of the gene were identified, four of which were unique. The regularities in the allele distribution in 37 genotypes were found to be in accor dance with their systematic positions. The trait was found to be broadly diverse both among the sections of the genus and within a particular section. Variants of the gene were identified in representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In previously studied Russian apple cultivars collection the most common were genotypes homozygous for allele 202 and 198 : 202 genotypes (Savel'ev et al, 2014a). At the same time, analysis of Md-Exp7 locus polymorphism in the Malus species representing four sections of the genus, showed that allele 202 was the most common and the authors suggested that this allele was the oldest one, while in species of section Malus that includes M. domestica, the most common were alleles 198, 202 and 204 bp (Savel'ev et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previously studied Russian apple cultivars collection the most common were genotypes homozygous for allele 202 and 198 : 202 genotypes (Savel'ev et al, 2014a). At the same time, analysis of Md-Exp7 locus polymorphism in the Malus species representing four sections of the genus, showed that allele 202 was the most common and the authors suggested that this allele was the oldest one, while in species of section Malus that includes M. domestica, the most common were alleles 198, 202 and 204 bp (Savel'ev et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…The allelic composition of studied apple cultivars for the SSR marker was associated with differences in fruit softening: 198 bp (best firmness retention), 202 bp (intermediate) and 214 bp (worst) (Costa et al, 2008). Later screening of apple cultivars and species collections revealed some rare Md-Exp7 alleles with unknown effect on fruit softening (Nybom et al, 2012(Nybom et al, , 2013Savel'ev et al, 2014b).…”
mentioning
confidence: 99%
“…These genes have been mapped, the effect of allelic variants of genes on the level of endogenous ethylene synthesis in fruits and, accordingly, on the storage quality of fruits, has been established, and effective DNA markers for identifying alleles have been developed (Sunako et al, 1999;Oraguzie et al, 2004;Costa et al, 2005). Using these markers, allelic combinations in the breeding material and collection samples of the apple tree were assessed in the world (Oraguzie et al, 2007;Zhu, Barritt, 2008;Nybom et al, 2012;Suprun, Tokmakov, 2013;Savel'ev et al, 2014b;Lyzhin, Savelyeva, 2020;Shamshin et al, 2020). The influence of the Md-ACS3a gene on the synthesis of endogenous ethylene in fruits was also revealed (Bai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%